Electron‐Transport Materials in Perovskite Solar Cells. Issue 10 (25th July 2018) - Lian, Jiarong; Lu, Bing; Niu, Fangfang; Zeng, Pengju; Zhan, Xiaowei
Abstract: Perovskite solar cells (PSCs) based on organic–inorganic hybrid materials are a rising technology offering an alternative to silicon‐based solar cells. Electron‐transport materials (ETMs) are important for PSCs and have received much attention. Here, first, the development of the structure of PSCs, from which the ETM requirements would be derived, is briefly discussed. Second, the progress of ETMs in mesoscopic PSCs, as well as regular (n–i–p) and inverted (p–i–n) planar PSCs is surveyed and analyzed, in terms of the material requirements, inorganic ETMs, organic ETMs, and interfacial materials. Third, the advancement of PSCs without ETMs is discussed. Finally, a summary and outlook on the current challenges and future development of ETMs in PSCs is given. Abstract : The electron transport materials (ETMs) in mesoscopic and planar perovskite solar cells (PSCs) with regular and inverted structures are reviewed; the comparison between organic and inorganic ETMs is discussed; and the development perspective of ETM‐free PSCs is forecast.